Large cell neuroendocrine carcinoma of cervix: A case report (Indian Journal of Case Reports, 2022)
Neuroendocrine carcinoma of the cervix is a rare aggressive tumor with a poor prognosis. Neuroendocrine carcinomas account for 1–1.5% of cervical cancer and around 12.5% were of large cell types. We report the case of a 55-year-old woman who came with complaints of pain abdomen and was reported as large cell neuroendocrine carcinoma of the cervix on biopsy. Immunohistochemistry was done which confirmed the diagnosis.